RETRACTED: COL10A1-DDR2 axis promotes the progression of pancreatic cancer by regulating MEK/ERK signal transduction - Wen, Zhihui; Sun, Jingbo; Luo, Junjie; Fu, Yun; Qiu, Yue; Li, Yanyan; Xu, Yangwei; Wu, Hongmei; Zhang, Qingling (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignant tumours with a poor prognosis. Type X collagen α 1 chain (COL10A1), a member of the collagen family, is a gene associated with the progression of a variety of human tumours, but the specific function and molecular mechanism of COL10A1 in pancreatic cancer remain unclear. Our study found that COL10A1 is highly expressed in pancreatic cancer cells and tissues, and its high expression is related to poor prognosis and some clinicopathological features, such as tumour size and differentiation. Biological functional experiments showed that overexpression of COL10A1 enhanced the proliferation and migration of PDAC cells. Interestingly, discoid protein domain receptor 2 (DDR2), the receptor of COL10A1, is regulated by COL10A1. We found that the COL10A1-DDR2 axis activates the mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK) pathway, which leads to epithelial-mesenchymal transformation (EMT) and accelerates the progression of pancreatic cancer. In summary, COL10A1 regulates cell proliferation and MEK/ERK signalling pathways by binding to DDR2 to promote migration, invasion and EMT. Our study suggested that COL10A1 might be a key factor in promoting PDAC progression. More research is needed to confirm COL10A1 as a potential biomarker and therapeutic target for PDAC.